Association Between Door to Balloon Time and Reperfusion with Left Ventricular Function and Heart Failure in Patients With ST Segment Elevated Myocardial Infarction Treated with Primary Percutaneous Intervention - Taha, Muhammad; Ahmad, Sajjad; Javeed, Muhammad; Kamran, Muhammad; ., Hamayon; Din, Syed Jalal Ud (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the association between prolonged D2B time and heart failure in patients with STEMI treated with primary PCI.Study Design: Prospective longitudinal studyPlace and Duration of Study: Cardiology department of Punjab Institute of Cardiology, Lahore Pakistan, from Oct 2024 to Feb 2025.Methodology: This study was carried out on 120 patients diagnosed with acute STEMI undergoing primary PCI after taking informed consent. Data was collected using pre-designed proforma. Patients were categorized into two groups based on door-to-balloon time, to compare the incidence of heart failure at 48 hours post-PCI.  Relative risk was calculated, and data analysis was performed using SPSS version 26, with p-value